Supramolecular Polymerization in Microfluidic Channels: Spatial Control Over Multiple Intermolecular Interactions. Issue 38 (19th August 2013) - Numata, Munenori; Kozawa, Tomohiro
<x xml:space="preserve">Abstract</x> A novel supramolecular assembly has been developed in conjugation with microfluidics. Self‐assembly of the programmed molecules was controlled precisely, in space and time, in a microflow channel as a result of a homogeneous solvent mixing process (see figure). Furthermore, through continuous organization of component molecules followed by orientation along microflow, the self‐assembling event containing different molecules was spatially controlled from nano to micrometer scale in a single stream (GMP=guanosine 5′‐monophosphate).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>